The association of sepsis bundle compliance with mortality in patients with ICU-acquired sepsis: a cohort study - Adam Green; Sharad Patel; Pamela Crabtree; Divyesha Patel; Andrew Hoke; Ricardo Jaime Orozco; George Sangah; Alvin Mercado; Nicole Melchiorre; Mariane Charron; Abhimanyu Chandel; Nitin Puri (BMC Infectious Diseases)
Abstract Background The efficacy of the SEP-1 Bundle has been questioned in the treatment of patients with hospital-acquired sepsis. We aimed to investigate bundle compliance and its association with survival in a subset of patients with HA sepsis: those with ICU-acquired sepsis. Methods A single-center retrospective cohort study was conducted in a tertiary care referral hospital. Adult patients diagnosed with ICU-acquired sepsis between 1 January 2019 and 31 December 2022 were identified. Survival to hospital discharge adjusted for disease severity based on 3-hour, 6-hour, and total bundle compliance was calculated. Secondary outcomes included the need for mechanical ventilation, vasopressors, initiation of acute hemodialysis, and discharge location. Results Of 191 patients with ICU-acquired sepsis, 61 patients (31.9%) demonstrated total bundle compliance. There was no difference in survival based on the unadjusted analysis of 3-hour bundle compliance, compliant versus non-compliant (78.9% vs. 67.0%; P = 0.100). However, there was a survival benefit in 6-hour and total bundle, compliance versus non-compliance (82.2% vs. 60.0%, P < 0.001; 86.9% vs. 64.6%, P = 0.002). When adjusted for SOFA and CCI, logistic regression demonstrated similar results: 3-hour compliance (OR: 0.60; 95% CI: 0.29–1.18, P = 0.150), 6-hour compliance (OR: 0.35; 95% CI: 0.17–0.68, P = 0.002) and total compliance (OR: 0.31; 95% CI: 0.13–0.69, P = 0.006). Components of the SEP-1 Bundle that showed a mortality benefit included the collection of “blood cultures prior to antibiotic administration” (OR: 0.46; 95% CI 0.22–0.96, P = 0.037) and “tissue perfusion assessment” (OR: 0.41; 95% CI 0.18–0.90, P = 0.028). Conclusions Six-hour and total SEP-1 bundle compliance was associated with increased hospital survival in patients with ICU-acquired sepsis. These findings suggest the importance of sepsis bundle compliance in the ICU environment. Clinical Trial Number Not Applicable.